An Analysis of Voice Spectrum Characteristics to the Male Voices Recording Using Praat Software - Asep Surahman (IJFL (International Journal of Forensic Linguistic), 2022)
This study is aimed to analyze the characteristics of male voices recording by using PRAAT software. Technically, this study was conducted by using direct measurement method with the assistance a laptop equipped with PRAAT software. In addition, the data were collected from the sound of men which has recorded by using a recording application which is available on smartphone that has been connected to a laptop. The sample of men voices consist one native speaker and 3 non-native speakers from the range age 22 to 30 years old. The basic frequency values ​​obtained from the voice recordings were compared between the voices of native and non-native speakers, the formant values ​​were obtained and the duration of time required in pronunciation. As result, this study found that the average basic frequency value for men (native speaker) shows a value that is almost the same as the basic frequency value for non-native speakers, it is caused by the shape of the sound-producing organs and conditions when recording sound. The value of the first formant (F1) and the fourth formant (F4) in men (native speaker) very flexible can be lower, higher and even the same to the non-native speaker. Therefore, the value of pitch and formant and the spectrum which has shown on PRAAT do not show the consistency and validity of the data so that in-depth analysis is needed with the help of other supporting media.